2022
DOI: 10.1038/s41598-022-14581-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of extensively drug resistant-tuberculosis in Western Cape Province, South Africa

Abstract: Tuberculosis (TB) remains a leading infectious disease killer globally. Treatment outcomes are especially poor among people with extensively drug-resistant (XDR) TB, until recently defined as rifampicin-resistant (RR) TB with resistance to an aminoglycoside (amikacin) and a fluoroquinolone (ofloxacin). We used laboratory TB test results from Western Cape province, South Africa between 2012 and 2015 to identify XDR-TB and pre-XDR-TB (RR-TB with resistance to one second-line drug) spatial hotspots. We mapped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Past studies also found that mutations in the region of the rpoB gene represented by probes E and D were the most common [39,40]. The Western Cape province had the highest detection rate of RR Mtb with probe E, followed by parts of KwaZulu Natal and Mpumalanga, areas where previous studies have reported high levels of drug-resistant Mtb [41][42][43][44]. The KwaZulu Natal and Mpumalanga provinces border Swaziland, which previously reported the unreliability of Xpert in identifying the rpoB 1491F mutation [45].…”
Section: Discussionmentioning
confidence: 90%
“…Past studies also found that mutations in the region of the rpoB gene represented by probes E and D were the most common [39,40]. The Western Cape province had the highest detection rate of RR Mtb with probe E, followed by parts of KwaZulu Natal and Mpumalanga, areas where previous studies have reported high levels of drug-resistant Mtb [41][42][43][44]. The KwaZulu Natal and Mpumalanga provinces border Swaziland, which previously reported the unreliability of Xpert in identifying the rpoB 1491F mutation [45].…”
Section: Discussionmentioning
confidence: 90%